2007
DOI: 10.17221/1849-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Results of an orchard trial with new clonal sweet cherry rootstocks established at Holovousy and evaluated in the stage of full cropping

Abstract: Several series of dwarfing rootstocks were bred in research institutes and universities all over the world in the 1960s and 1970s. These series were reviewed by Bujdosó and Hrotkó (2005). Since 1994 international cherry rootstock trials in Europe were co-ordinated by the Danish Institute of Plant and Soil Science at Aarslev, Denmark. The Research and Breeding Institute of Pomology Holovousy Ltd. has jointed these trials as one of their partners and established an experimental orchard with a range of selected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…Impact of some rootstocks on earlier start of fruit ripening observed in this study was already recorded in our previous observations (Blažková, Hlušičková 2007). There the span of the mean time of fruit ripening of Lapins cultivar on tested rootstocks was equal to 2.3 days.…”
Section: Time Of Ripeningsupporting
confidence: 81%
See 2 more Smart Citations
“…Impact of some rootstocks on earlier start of fruit ripening observed in this study was already recorded in our previous observations (Blažková, Hlušičková 2007). There the span of the mean time of fruit ripening of Lapins cultivar on tested rootstocks was equal to 2.3 days.…”
Section: Time Of Ripeningsupporting
confidence: 81%
“…Differences in the start of flowering caused by rootstocks in this study were much less than those from our previous trials or found already in Germany (Blažková, Hlušičková 2007). This is evidently connected to the limited number of rootstocks and to the selection used in this study.…”
Section: Time Of Floweringcontrasting
confidence: 66%
See 1 more Smart Citation
“…Dwarf trees have a greater proportion of well illuminated canopy, low spray solution and higher labor efficiency. Rootstock influenced the tree growth (Cantin et al, 2010;Blazkova and Hlusickova, 2007), yield performance (Moreno et al, 2001), fruit quality (Whiting et al, 2005, Usenik et al, 2010, Lanauskas et al, 2012. Sansavini et al, (2001), reported, when 'Burlat 1', 'Durone Compatta di Vignola', 'Lapins' and 'Van' grafted on 20 clonal rootstock and planted in HDP system, bearing starts 4-5 years after planting and tree attained full bearing (10 kg tree -1 ) after 7-8 years.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these trees are frequently more vulnerable to various stressors and especially to the dryness of soil. In such situations, the growth of trees is often poor and the size of fruits is too small (Edin et al 1998;Modl 2000;Blažková 2001;Bujdosó et al 2004;Blažková, Hlušičková 2004, 2007a. For these reasons, many cherry growers have focused on the construction of irrigation, which was not necessary for the crop in this country before.…”
mentioning
confidence: 99%